2018
DOI: 10.1002/smtd.201700392
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome the Limitations of AIEgens in Biomedical Applications

Abstract: NPs), [7][8][9][10] fluorescent proteins (FPs), [11,12] conjugated polymer NPs, [13] dye-loaded polymer NPs, [14] and lipid NPs [15] have been exploited in biomedical applications. QDs have bright fluorescence and are generally photostable under various biological conditions. To date, it is well understood that their toxicity is a major concern for translating them for clinical research. [16,17] It is also worth noting that many surfactants used currently for the synthesis of inorganic or organic NPs, e.g., so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 96 publications
(134 reference statements)
0
31
0
Order By: Relevance
“…[ 11,12 ] Given the circumstances, emerging research interest is the aggregation‐induced emission (AIE), which refers to a photophysical phenomenon wherein a novel family of propeller‐shaped luminogens with twisted structural conformation are weakly emissive or nonemissive in the single‐molecule state, but are induced to emit intensely in the aggregates through a mechanism of the restriction of intramolecular motions (RIM). [ 13–23 ] AIE luminogens (AIEgens) have triggered state‐of‐the‐art developments in FLI, thanks to their intrinsic properties including high signal‐to‐noise ratio and high photostability. In addition, recent advances have demonstrated that AIEgens can also serve as phototheranostic agents for multimodal imaging‐guided synergistic therapy through rational molecular design, benefiting from the inherent capabilities of AIEgens as an extraordinary template for subtly regulating the balance between radiative and nonradiative decays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11,12 ] Given the circumstances, emerging research interest is the aggregation‐induced emission (AIE), which refers to a photophysical phenomenon wherein a novel family of propeller‐shaped luminogens with twisted structural conformation are weakly emissive or nonemissive in the single‐molecule state, but are induced to emit intensely in the aggregates through a mechanism of the restriction of intramolecular motions (RIM). [ 13–23 ] AIE luminogens (AIEgens) have triggered state‐of‐the‐art developments in FLI, thanks to their intrinsic properties including high signal‐to‐noise ratio and high photostability. In addition, recent advances have demonstrated that AIEgens can also serve as phototheranostic agents for multimodal imaging‐guided synergistic therapy through rational molecular design, benefiting from the inherent capabilities of AIEgens as an extraordinary template for subtly regulating the balance between radiative and nonradiative decays.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Given the circumstances, emerging research interest is the aggregation-induced emission (AIE), which refers to a photophysical phenomenon wherein a novel family of propeller-shaped luminogens with twisted structural conformation are weakly emissive or nonemissive in the single-molecule state, but are induced to emit intensely in the aggregates through a mechanism of the restriction of intramolecular motions (RIM). [13][14][15][16][17][18][19][20][21][22][23] AIE luminogens (AIEgens) have triggered state-ofthe-art developments in FLI, thanks to their intrinsic properties including high signal-to-noise ratio and high photostability.…”
mentioning
confidence: 99%
“…Through long‐term mechanistic investigations of structure–property relationships, it has come to light that the restriction of intermolecular rotations and twisted intramolecular charge transfer (TICT) contribute to enhanced emission quantum yield, accompanied by prevention of excimers, formation of aggregates, and intermolecular charge transfer . To date, thousands of papers have bloomed in this hot area of AIE and hundreds of reviews have summarized various applications, such as in polymer chemistry, biovisualization, photodynamic therapy, and OLEDs . Additionally, it is AIE that could produce impressive electrochemiluminescence (abbreviated as ECL, also called electrogenerated chemiluminescence).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dye-loaded polymer NPs have recently achieved very high brightness equivalent to 100-1000 organic dyes. [9][10][11] Achieving such high brightness required the development of new strategies to overcome aggregation-caused quenching of the fluorophores encapsulated at very high concentrations in the polymer matrix of NPs. This was achieved, for example, by using fluorophores that undergo aggregation-induced emission 12 or by using salts of fluorophores with hydrophobic bulky counterions to prevent aggregation.…”
Section: Introductionmentioning
confidence: 99%